Analisis Pembelajaran Membatik Peserta Sanggar Bstik Kembang Mayang Di Kota Tanggerang - azhariyah, royhanatul (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
This study aims to analyze the inhibiting and supporting factors in batik learning so that batik learning at the Kembang Mayang Batik Studio can be further developed. The research method used qualitative methods with a case study approach with data collection techniques of observation, interviews and documentation. The data obtained was then reduced. The existence of this research aims to develop the creativity and skills of the participants of the Kembang Mayang Batik Studio, apart from that this research analyzes the supporting and inhibiting factors of batik learning for participants of the Kembang Mayang Batik Studio. The method used is a qualitative method with a case study approach, by collecting data through observation techniques, documentation and interviews with the studio and participants. Then the data is processed with triangulation techniques. The measuring instrument used to assess refers to eight aspects of learning. The results of the study show that there are several aspects of learning used, including the presence of participants and educators, the use of learning materials, collaborated learning methods, and evaluation. These aspects are supporting aspects, while inhibiting aspects include learning objectives, curricula, and learning media. The results of the evaluation of the participants' work reached 86.